Prevalence and Detection of Stenotrophomonas maltophilia Carrying Metallo-β-lactamase blaL1 in Beijing, China - Yang, Zhan; Liu, Wei; Cui, Qian; Niu, Wen K.; Li, Huan; Zhao, Xiang N.; Wei, Xiao; Wang, Xue S.; Huang, Si M.; Dong, De R.; Lu, Si J.; Bai, Chang Q.; et al. (Frontiers in Microbiology, 2014)
Intrinsic β-lactam resistance in Stenotrophomonas maltophilia S. maltophilia is caused by blaL1 and/or blaL2, a kind of metallo-β-lactamase with a broad substrate spectrum including carbapenems. A rapid and sensitive molecular method for the detection of blaL1 in clinical samples is needed to guide therapeutic treatment. In present study, we first described a loop-mediated isothermal amplification (LAMP) method for the rapid detection of blaL1 in clinical samples by using two methods including a chromogenic method using calcein/Mn2+ complex and the real-time turbidity monitoring to assess the reaction. Then dissemination of L1-producing S. maltophilia was investigated from ICU patients in three top hospital in Beijing, China. The results showed that both methods detected the target DNA within 60 min under 65°C. The detection limit of LAMP was 3.79 pg/µl DNA, and its sensitivity 100-fold greater than that of conventional PCR. All 21 test strains except for S. maltophilia were negative for blaL1, indicative of the high-specificity of the primers for the blaL1. A total of 22 L1-positive isolates were identified for LAMP-based surveillance of blaL1 from 105 ICU patients with clinically suspected multi-resistant infections. The sequences of these blaL1 genes were conservative with only a few sites mutated, and the strains had highly resistant to β-lactam antibiotics. The MLST recovered that 22 strains belonged to seven different ST types. Furthermore, co-occurrence of blaL1 and blaL2 genes were detected in all of isolates. Strikingly, S. maltophilia DCPS-01 was recovered to contain blaL1, blaL2, and blaNDM‑1 genes, possessing an ability to hydrolyse all β-lactams antibiotics. Our data showed the diversity types of S. maltophilia carrying blaL1 and co-occurrence of many resistant genes in the clinical strains signal an ongoing and fast evolution of S. maltophilia resulting from their wide spread in the respiratory infections, and therefore will be difficult to control.